DUTIES OF PROFESSIONAL COUNSELLORS IN PROMOTING UNITY IN NIGERIA - BOLU-STEVE, F. N.; AJOKPANIOVO, Micheal; ADEBOYE, A. (Ilorin Journal of Education, 2023)
In Nigeria, there are issues of insecurity, disintegration, lawlessness and heightened corruption among others. The input of professional counsellors cannot be overemphasized especially when stakeholders are formulating policies for national integration. Hence, it is on this premise that this study investigated the role of counsellors in promoting Unity in Nigeria. The research design adopted for the study was the descriptive survey type. A multi-stage sampling procedure was adopted in selecting the respondents that participated in the study. Purposive sampling technique was used to select 460 respondents for the study. The instrument used in gathering the required data was a self-developed questionnaire titled Duties of Counsellors in Promoting Unity Questionnaire (DCPUQ). Three null hypotheses were generated and tested at 0.05 alpha level of significance using t-test statistical tool. The result obtained revealed that there was significant difference in the role of counsellors in promoting unity based on gender, educational qualification and length of years in service. Based on the findings of the study, it was recommended that more school counsellors should enlighten the students on the need for unity and integration among Nigerians. Seminars and workshops should be organized by counsellors in collaboration with the government, Non-Governmental Organizations and other stakeholders in order to discuss and tackle contemporary issues on National integration and unity.